2013
DOI: 10.1371/annotation/95cefb34-2f3d-42a5-b73e-53c531591f0b
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Doxorubicin-Mediated Bone Loss in Breast Cancer Bone Metastases Is Driven by an Interplay between Oxidative Stress and Induction of TGFβ

Abstract: Breast cancer patients, who are already at increased risk of developing bone metastases and osteolytic bone damage, are often treated with doxorubicin. Unfortunately, doxorubicin has been reported to induce damage to bone. Moreover, we have previously reported that doxorubicin treatment increases circulating levels of TGFb in murine pre-clinical models. TGFb has been implicated in promoting osteolytic bone damage, a consequence of increased osteoclast-mediated resorption and suppression of osteoblast different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…As TGF-β is reported to inhibit the expression of RUNX2 [169], it seems relevant that impairing the TGF-β pathway may have a critical influence on osteoblastic differentiation. This hypothesis was recently verified by Rana et al, who observed that impairing the TGF-β pathway through the use of an anti-TGF-β antibody improves doxorubicin-mediated inhibition of osteoblastic differentiation and increases the frequency of osteoblast colony-forming units [170]. In addition, the anti-osteoblastic-differentiation role of the TGF-β pathway was supported by Maeda et al [171].…”
Section: The Transforming Growth Factor-β (Tgf-β) Pathwaymentioning
confidence: 76%
“…As TGF-β is reported to inhibit the expression of RUNX2 [169], it seems relevant that impairing the TGF-β pathway may have a critical influence on osteoblastic differentiation. This hypothesis was recently verified by Rana et al, who observed that impairing the TGF-β pathway through the use of an anti-TGF-β antibody improves doxorubicin-mediated inhibition of osteoblastic differentiation and increases the frequency of osteoblast colony-forming units [170]. In addition, the anti-osteoblastic-differentiation role of the TGF-β pathway was supported by Maeda et al [171].…”
Section: The Transforming Growth Factor-β (Tgf-β) Pathwaymentioning
confidence: 76%
“…It was shown that doxorubicin induced decreases of osteoblast survival and differentiation in the previous report [19]. Significant changes were observed from 10 μg/mL groups, so that we used this concentration for experiments in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Another important factor in bone marrow metastases is oxidative stress: for example, the known chemotherapeutic agent doxorubicin, although helpful as cancer drug, has been shown to cause bone loss due to induction of oxidative stress in osteoclasts in vitro, which causes an increase in their activity. TGF-β also seems to be involved in this process [57]. Consistently, treating neuroblastoma cells in vitro with an antioxidant can impair their growth [58].…”
Section: Molecular Mechanisms Of Bone Metastasesmentioning
confidence: 99%